Diffusion Approximation with Equilibrium for Evolutionary Systems Switched by Semi-Markov Processes - Korolyuk, V. S.; Limnios, N. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider an evolutionary system switched by a semi-Markov process. For this system, we obtain an inhomogeneous diffusion approximation results where the initial process is compensated by the averaging function in the average approximation scheme.